Development and validation of a PMA-qPCR method for accurate quantification of viable Lacticaseibacillus paracasei in probiotics - Guo, Lizheng; Ze, Xiaolei; Jiao, Yingxin; Song, Chengyu; Zhao, Xi; Song, Zhiquan; Mu, Shuaicheng; Liu, Yiru; Ge, Yuanyuan; Jing, Yu; Yao, Su (Frontiers in Microbiology, 2024)
The effectiveness of probiotic products hinges on the viability and precise quantification of probiotic strains. This study addresses this crucial requirement by developing and validating a precise propidium monoazide combination with quantitative polymerase chain reaction (PMA-qPCR) method for quantifying viable Lacticaseibacillus paracasei in probiotic formulations. Initially, species-specific primers were meticulously designed based on core genes from the whole-genome sequence (WGS) of L. paracasei, and they underwent rigorous validation against 462 WGSs, 25 target strains, and 37 non-target strains across various taxonomic levels, ensuring extensive inclusivity and exclusivity. Subsequently, optimal PMA treatment conditions were established using 25 different L. paracasei strains to effectively inhibit dead cell DNA amplification while preserving viable cells. The developed method exhibited a robust linear relationship (R² = 0.994) between cycle threshold (Cq) values and viable cell numbers ranging from 10³ to 10⁸ CFU/mL, with an impressive amplification efficiency of 104.48% and a quantification limit of 7.30 × 10³ CFU/mL. Accuracy assessments revealed biases within ±0.5 Log10 units, while Bland-Altman analysis demonstrated a mean bias of 0.058 Log10, with 95% confidence limits of -0.366 to 0.482 Log10. Furthermore, statistical analysis (P = 0.76) indicated no significant differences between theoretical and measured values. This validated PMA-qPCR method serves as a robust and accurate tool for quantifying viable L. paracasei in various sample matrices, including pure cultures, probiotics as food ingredients, and composite probiotic products, thereby enhancing probiotic product quality assurance and contributing to consumer safety and regulatory compliance.